2003
DOI: 10.1248/bpb.26.631
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Some Azines of Acetophenone Derived Mono-Mannich Bases against Jurkat Cells

Abstract: Mannich bases have several biological activities such as antimicrobial, [1][2][3][4][5] cytotoxic, [6][7][8][9] anticancer, 10) analgesic, 11) anti-inflammatory, 12,13) diuretic 14,15) and anticonvulsant [16][17][18][19] activities. An amino ketone, Mannich base, containing at least one activated hydrogen atom at the b position to an amino function, can undergo deamination in vivo 20) or under simulated in vitro conditions 1,3,6) to liberate the corressponding a,b-unsaturated ketones. The a,b-unsaturated keton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
1
30
0
4
Order By: Relevance
“…According to the studies carried out, the following activities of Mannich bases have been identified: anticancer 4 , cytotoxic [5][6][7][8][9][10][11][12][13] , anti-inflammatory [14][15][16] , anticonvulsant 17,18 and antifungal 19,20 . Their cytotoxic activities were attributed to the a,b-unsaturated ketone, which is available in the chemical structure of the compound or to the product produced by deamination process in vivo or under simulated conditions in vitro 7,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies carried out, the following activities of Mannich bases have been identified: anticancer 4 , cytotoxic [5][6][7][8][9][10][11][12][13] , anti-inflammatory [14][15][16] , anticonvulsant 17,18 and antifungal 19,20 . Their cytotoxic activities were attributed to the a,b-unsaturated ketone, which is available in the chemical structure of the compound or to the product produced by deamination process in vivo or under simulated conditions in vitro 7,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Ketazines, mixed azines, and cyclic compounds have exhibited antitumor [7][8][9][10][11][12], anti-bacterial [13][14][15][16][17][18][19][20], anti-inflammatory [21], antimalarial dyes [22], anticonvulsant [23,24], insect growth regulators [25] and many other activities. Contrary, acyclic aldazines are much less studied.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The bioactivity of Mannich ketones may be due to the alkylating ability of a,b-unsaturated ketones that are liberated in situ following deamination (Fig. 1).…”
mentioning
confidence: 99%
“…1). 2,4,[7][8][9][10][11] Various studies on Mannich ketones have been reported from our laboratory [1][2][3][4][5][6] but toxicities 7,8) associated with this class of compounds have discouraged us to pursue them further. The unwanted toxicities associated with the Mannich ketones may be due to the rapid decomposition to form a reactive enone which is sequestered indiscriminately with cellular nucleophiles.…”
mentioning
confidence: 99%